APLIKASI BEBERAPA DOSIS TRICHO-KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) PADA TANAMAN PAKCOY (Brassica rapa L.) - Dahlan, Kasrul Akbar; Puspita, Fifi; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Pakcoy is a type of mustard are cultivated by farmers. Plants pakcoy seen from the economic and business aspects should be developed to meet consumer demand higher and higher so that the necessary technical good farming. One of them with fertilization. Fertilizer that can be used for cultivation pakcoy one of them is by using Tricho - compost TKKS . This study aimed to determine the effect Tricho - compost application and get a better dose on growth and production Pakcoy . This study used a randomized block design (RBD ) consists of 5 treatments with 4 replicates . The treatment being tested is the use of multiple doses of Tricho - compost TKKS namely providing Tricho - compost TKKS with doses of 0 ( no Tricho - compost EFB ), 3, 6, 9 and 12 tons / ha. Data were analyzed by analysis of variance and tested further by a further test DNMRT. The results showed multiple dose administration of Tricho - compost TKKS showed different effects on parameters of plant height, plant fresh weight and fresh weight of plants suitable for consumption, while for the parameter number and leaf area and root crown ratio did not show a different effect. Tricho - compost dosing TKKS with a dose of 9 tons / dose constitutethe best dose for plant height parameters, plant freshweightandplantfreshweight ofconsumable. Keywords: Tricho-compost, dose, growth, production.